(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study has been conducted to measure awareness status of Noise Pollution among the population of Poonch Town of Jammu and Kashmir, India. The result of the generated data regarding impact/awareness of noise pollution revealed that majority of the respondents were having the knowledge of noise pollution and were confronting the problem of noise pollution. According to the majority of respondents, vehicular/traffic noise loudspeakers, construction and commercial operations, generators, agricultural implements, and other sources were the main causes of noise pollution in the area. Noise has an impact on a person’s overall wellbeing and is a potential risk to one health, both physically and psychologically. Therefore it is the need of the hour to take preventive measures and effective mitigation strategies so as to mitigate the detrimental effects of noise menace. The difference in responses between male and female respondents was statistically insignificant (p > 0.05).